2007
DOI: 10.1177/1753465807082374
|View full text |Cite
|
Sign up to set email alerts
|

Review: Systemic consequences of COPD

Abstract: Chronic obstructive pulmonary disease (COPD) is a highly prevalent chronic lung condition, affecting ∼10% of adults over the age of 40 years in the western world. Research over the past 10 years has shown that COPD is more than just a lung disorder; it affects other end-organs including the cardiovascular and the musculoskeletal systems, making it a multi-component, multi-system disease. COPD increases the risk for ischemic heart disease, stroke, osteoporosis, cachexia, and muscle weakness by two to threefold,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 84 publications
0
12
0
1
Order By: Relevance
“…However, it remains unclear whether systemic inflammation is a cause of cardiovascular disease, or merely a marker [27]. In any case, over the past 5 years, several other plausible explanations, such as increased oxidative stress, neurohumoral disturbances, and increased thrombotic tendency, have been provided [28]. All are very intriguing, but none is really definite.…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains unclear whether systemic inflammation is a cause of cardiovascular disease, or merely a marker [27]. In any case, over the past 5 years, several other plausible explanations, such as increased oxidative stress, neurohumoral disturbances, and increased thrombotic tendency, have been provided [28]. All are very intriguing, but none is really definite.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that impaired lung functioning causes changes in the central nervous system through processes such as cerebral diseases resulting from impaired fibrinolytic activity, oxidate stress, [99] vascular diseases, and increased proinflammatory cytokines such as TNFR1 that act as a possible systemic mediator via cardiovascular disease between lung functions and brain [45]. Increases in the circulating levels of thrombotic factors may be expected to elevate the risk for cardiovascular disease [104]. In other words, cognitive deficits are mediated by the presence of changes in systemic hemodynamic and cerebral diseases.…”
Section: Mechanism Of Cognitive Impairment In Copd and Osas Patientsmentioning
confidence: 99%
“…En EPOc avanzada es común la pérdida de peso y la caquexia. también se observa, en mayor proporción respecto población de edad similar, una disminución de la masa muscular y mayor frecuencia de comorbilidades como osteoporosis, insuficiencia cardiaca, enfermedad cardiaca isquémica, accidente vascular cerebral, depresión y cáncer 33 . Un estudio español 34 , mostró en pacientes con EPOc exacerbado una alta frecuencia de hipertensión arterial, de insuficiencia cardiaca y de diabetes mellitus.…”
Section: Comorbilidades Y Consecuencias Sistémicasunclassified